Integral Practice of School Principal Leadership. The Application of Ken Wilber's Conception - Piotr Błajet; Beata Przyborowska (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2016)
To reach the integral level, one has to obtain body and mind awareness, activate consciousness and internal vigilance, take care of each sphere of his/her existence and create a higher quality of life. Our project, implemented within the frameworks of the postgraduate studies for school principals, was focused on emphasising these issues. During the course of conversations and the final exam, we managed to show the students different perspectives of perceiving the reality and look at our private and professional life from the integral perspective.